Developing Design Principles for Green IS Facilitating Sustainable User Behavior: A Design Science Research Approach - Weigl, Johanna; Haag, Steffi (17th International Conference on Wirtschaftsinformatik, WI 2022, 2022)
The health of ecosystems is vital for the existence of human life on our planet. As we witness large-scale deterioration of the natural environment, consequences of climate change call for innovative solutions to guide the process of sustainable development. Despite the critical role of information systems (IS) for facilitating sustainable action, research on Green IS in this context has been limited. Our study addresses the question of how to design Green IS for sustainable user behavior by following a design science research approach. In particular, we derive and evaluate theory-based design principles that promote sustainable user behavior with respect to responsible consumption.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Design Science Research; Green Information Systems; Sustainable Human Computer Interaction; Sustainable User Behavior